Ichthyotherapy as Alternative Treatment for Patients with Psoriasis: A Pilot Study. Issue 4 (2006) - Grassberger, Martin; Hoch, W.
Abstract : Ichthyotherapy (therapy with the so-called 'Doctorfish of Kangal', Garra rufa ) has been shown to be effective in patients with psoriasis in the Kangal hot springs in Turkey. This study evaluates the efficacy and safety of ichthyotherapy in combination with short-term ultraviolet A sunbed radiation in the treatment of psoriasis under controlled conditions. We retrospectively analyzed 67 patients diagnosed with psoriasis who underwent 3 weeks of ichthyotherapy at an outpatient treatment facility in Lower Austria between 2002 and 2004. Main outcome measures are as follows: overall relative reduction in Psoriasis Area Severity Index (PASI) score; proportion of patients with an improvement in their PASI score of ≥75% (PASI-75) and ≥50% (PASI-50); patient-reported outcomes assessed with a custom questionnaire; and patient follow-up with a questionnaire sent out in March 2005. Safety was evaluated by reviewing adverse events and vital signs. Overall there was a 71.7% reduction in PASI score compared to baseline ( P < 0.0001). Of the 67 patients studied, 31 (46.3%) achieved PASI-75 and 61 patients (91%) achieved at least PASI-50. Patients reported substantial satisfaction with the treatment. The reported mean remission period was 8.58 months [95% confidence interval (CI) 6.05–11.11]. A total of 87.5% of patients reported a more favorable outcome with ichthyotherapy, when asked to compare ichthyotherapy to other previously tried therapies. Sixty-five percent stated that after the relapse their symptoms were less severe than before treatment. There were no significant adverse events. The benefit demonstrated in this study along with the favorable safety profile suggests that ichthyotherapy could provide a viable treatment option for patients with psoriasis.